Paradigma Integratif Manajemen Sumber Daya Manusia Pendidikan Islam Berbasis Nilai Tauhid dan Kompetensi Profesional - Siswahyuningsih, Zahrotunnisa`; Maunah, Binti; Junaris, Imam (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This article examines the integrative paradigm in the management of human resources (HR) of Islamic education, which combines the values of monotheism and professional competence. The research method used is library research, with the process including analyzing various literature related to human resource management, Islamic education, and integrative paradigms. The results of the study show that the integrative paradigm emphasizes the development of human beings, namely individuals with a balance of intellectual, emotional, and spiritual intelligence. The application of this paradigm involves the integration of Islamic values such as trust, justice, and deliberation in every aspect of HR management, from recruitment to career development. Challenges in the implementation of this paradigm include resistance to change and lack of understanding of the concept of integration. The solutions offered include comprehensive training and development, as well as the formation of an organizational culture that supports Islamic values. This article concludes that the integrative paradigm is a relevant approach to manage Islamic education human resources in the era of globalization, with the aim of improving the quality of educators and education personnel with noble character. This study formulates three fundamental principles of the integrative HR paradigm, namely the foundation of monotheism, morality-based professionalism, and orientation to Kamil people. Practically, these principles serve as a strategic guide for education managers to transform human resource management from just an administrative function to a process of building superior character and noble character.